Altered decidual leucocyte populations in the placental bed in pre-eclampsia and foetal growth restriction: a comparison with late normal pregnancy - Williams, Paula J; Bulmer, Judith N; Searle, Roger F; Innes, Barbara A; Robson, Stephen C (Reproduction (Cambridge, England), 2009)
Alterations in the balance of leucocyte populations in uterine decidua may lead to the generation of an unfavourable cytokine environment that is associated with unsuccessful pregnancy. Single and double immunohistochemical labelling was used to examine leucocyte populations in decidua from normal third trimester, foetal growth-restricted and pre-eclamptic pregnancies. Placental bed biopsies from 12 women undergoing elective Caesarean section with no hypertension or foetal growth restriction (FGR), 8 women with FGR without maternal hypertension and 12 women with pre-eclampsia (PE) were used to quantify decidual CD56+ uterine NK cells, CD14+ macrophages, CD3+T-lymphocytes and CD8+ lymphocytes. CD3+CD56+, CD8+CD56+ and CD161+CD3+ double-labelled cells in decidua were compared in PE and control decidua. Decidual CD3+T-lymphocytes (P<0.01), CD8+ cytotoxic T-lymphocytes (P<0.05), CD14+ macrophages (P<0.0001) and CD56+ uterine natural killer (uNK) cells (P=0.01) were decreased in placental bed biopsies from women with PE compared with control third trimester decidua. By contrast, only CD56+ uNK cells were decreased in FGR decidua (P<0.05). Double-positive CD8+CD56+ cells were also decreased in PE compared with control third trimester decidua (P<0.05). The reduction in specific leucocyte subset numbers in PE and uNK cells in FGR suggests that altered local cytokine balance may be important in defective trophoblast invasion and spiral artery transformation in these pathological pregnancies.